Podobe raka - Žagar, Brina (Anthropos (Ljubljana), 2015)
In the paper illness representations are considered from the anthropological viewpoint. The central part is dedicated to the cancer representations and five dimensions of illness: identity (symptoms and label), cause, cure, time-line and consequences. The main emphasis is on the explanation of causes of illness and influences they have on individuals, and on how patients confront with the illness. Although illness representations are changing, these changes are slow and often do not follow new scientific discoveries. Many times they just reflect old viewpoints connected with taboos and stigmas. Illness representations are strongly present in our society and have a significant influence on how individuals and their surrounding accept the illness, explain it and cope with it. It is therefore of great importance to investigate these representations and recognize negative stereotypes and stigmas, as well as try to make people aware of them and make them disappear by providing more adequate information.
Keywords: rak (medicina); psihoonkologija; medicinska antropologija